Stigmatizing ‘evildoers’: how beliefs about evil and public stigma explain criminal justice policy preferences - Silver, Jason R. (Psychology, crime & law, 2025)
Characterizations of offenders as ‘evil’ appear in popular entertainment, political rhetoric, and scholarship and may be rooted in widely endorsed cultural narratives. Integrating psychological and criminological literatures, we argue that endorsement of good-and-evil myths may be associated with criminal justice policy support via stigmatizing attitudes about those who engage in crime. We partially tested these hypotheses in a preliminary study using an online convenience sample (recruited using Amazon MTurk in 2015), then tested the full theoretical model using more comprehensive measures in a survey of American adults conducted via Qualtrics Panel in 2021 (N = 1,162). We found that both belief in evil (i.e. belief in evil forces) and belief in redemptive violence (i.e. belief in a clash between good and evil) were positively associated with punitive policy support, and stigmatizing attitudes partially mediated the effects of both. While belief in redemptive violence was negatively associated with rehabilitative policy support and stigmatizing attitudes mediated that relationship, belief in evil was not associated with support for rehabilitation. We consider the implications of our findings for mitigating the harms of public stigma and punitive criminal justice policy.